Preliminary Studies of Air flow around Vehicle Front Windscreen - Abdul Munir, Fudhail; Mat Nuri @ Md Din, Nur Rashid; Mohd Azmi, Mohd Irwan; Salim, Mohd Azli; Hasnan, Mohd Yazid (2011)
In this project, simulation of air flow around vehicles frontal windscreen area was carried out. The vehicle models that had been chosen for this project were models from the national car manufacturer. ANSYS CFX software was used to run the simulation. Comparison of flow patterns and the velocity distribution were made for the corresponding vehicle models. The speed of the flow was set to be 90 km/h in the simulation. The main objective of this study is to obtain the flow pattern around a vehicle windscreen. The second objective is to determine the velocity distribution on the vehicle windscreen and factors affecting the velocity distribution. It was found that there are differences in term of flow patterns and velocity distribution with respect to the windscreen inclination angle.